2017
DOI: 10.1308/rcsann.2016.0347
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of incisional hernias following ileostomy reversal in colorectal cancer patients treated with anterior resection

Abstract: INTRODUCTION The aim of this study was to identify the rate of incisional hernia formation following ileostomy reversal in patients who underwent anterior resection for colorectal cancer. In addition, we aimed to ascertain risk factors for the development of reversal-site incisional hernias and to record the characteristics of the resultant hernias. MATERIALS AND METHODS Using a prospectively compiled database of colorectal cancer patients who were treated with anterior resection, we identified individuals who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
(32 reference statements)
2
20
1
1
Order By: Relevance
“…Hernias may be more common after reversal of large bowel ostomies principally because of the larger size of the abdominal wall defect. But even in studies including only loop ileostomy reversals, the incidences have been reported higher than in our study: 11.1% [19], 14.9% [13], and 23.9% [20], respectively. All of them primarily used CT scans for evaluation.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Hernias may be more common after reversal of large bowel ostomies principally because of the larger size of the abdominal wall defect. But even in studies including only loop ileostomy reversals, the incidences have been reported higher than in our study: 11.1% [19], 14.9% [13], and 23.9% [20], respectively. All of them primarily used CT scans for evaluation.…”
Section: Discussioncontrasting
confidence: 97%
“…Colostomies had a higher risk than ileostomies in Sharp et al [12], but in other studies a colostomy was a risk factor only in patients with malignant disease [17]. Other risk factors for developing hernia after stoma reversal that have been reported are surgical site infection [11,18], diabetes [12], age [12], urgent operation [12], longer time between primary surgery and reversal [13], and hypertension [17,20]. One study did not find any significant risk factors at all [19].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is interesting that hypertension is associated with abdominal wall failure, a relationship previously identified in our own work following loop ileostomy closure. The significance of BMI and hypertension appear to be overtaking smoking as a risk factor, as smoking was not a significant factor in this analysis or others. Optimizing BP and weight reduction are logical ways to reduce the incidence of hernia, as well as the selective use of prophylactic mesh implants in high‐risk patients.…”
mentioning
confidence: 59%